2004
DOI: 10.1270/jsbbs.54.1
|View full text |Cite
|
Sign up to set email alerts
|

Rice Retroposon p-SINE1 and Origin of Cultivated Rice

Abstract: The wild rice species Oryza rufipogon displays wide intraspecific variations. It is considered to be the progenitor of the cultivated rice species Oryza sativa with two ecotypes, japonica and indica. p-SINE1 is the first plant retroposon SINE identified in O. sativa and is present in strains of Oryza species with the AA genome in multiple copies. Some p-SINE1 members show interspecific insertion polymorphism among the rice strains and are thus assumed to be suitable markers for classifying the strains and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…In the paper of Morishima et al (1984), it was suggested that the intermediate plants are ecologically unstable and when disruptive selection is strong enough, they can be differentiated into perennial and annual types. Mochizuki et al, 1992;Motohashi et al, 1997;Cheng et al, 2002;Ohtsubo et al, 2004). There are 112 RA-subfamily members, including 64 RAα and 18 RAβ members.…”
Section: Resultsmentioning
confidence: 99%
“…In the paper of Morishima et al (1984), it was suggested that the intermediate plants are ecologically unstable and when disruptive selection is strong enough, they can be differentiated into perennial and annual types. Mochizuki et al, 1992;Motohashi et al, 1997;Cheng et al, 2002;Ohtsubo et al, 2004). There are 112 RA-subfamily members, including 64 RAα and 18 RAβ members.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar manner to the p-SINE1 members, the p-SINE2 and p-SINE3 members appear to be dispersed randomly along each of the 12 chromosomes ( Fig. 5; Ohtsubo et al, 2004), but unlike other retrotransposons and autonomous transposable elements that form a cluster in the heterochromatin of pericentromeric regions (Sasaki et al, 2002;Feng et al, 2002; The Rice Chromosome 10 Sequencing Consortium 2003). Of 17 p-SINE2 members, 10 were present in the putative or hypothetical exons or introns, or within a 0.5 kb region of genes or the putative coding regions (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…1), was identified in the introns of the Waxy gene in O. sativa (Umeda et al, 1991), and since then a large number of p-SINE1 members have been identified from rice species in the O. sativa and O. officinalis complexes (Mochizuki et al, 1993;Motohashi et al, 1997;Cheng et al, 2002Cheng et al, , 2003Xu, 2004). These include members of the RA (Recently Amplified) subfamily that consists of two groups, RA α and RA β (see Ohtsubo et al, 2004), most of which show insertion polymorphisms within O. sativa and its ancestral wild species O. rufipogon with the AA genome. The presence or absence of these polymorphic members has been used for phylogenetic analysis of strains in these species (Cheng et al, 2003;also Xu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…All O. rufipogon accessions used in this study were selected from core collection rank 1, 2, and 3, because these collection covered typical species-specific phenotypes and wide distribution in the habitat. AA genome species in the core collections are distinguished by SINE code which is the criteria of species based on the presence or absence of retrotransposon p-SINE insertions (Ohtsubo et al 2004). The genomic constitution, species name, habitat and SINE code of each accession are presented in Table 1.…”
Section: Plant Materialsmentioning
confidence: 99%